Current and Emerging Direct Oral Anticoagulants: State-of-the-Art - Lippi, Giuseppe; Gosselin, Robert; Favaloro, Emmanuel J. (Seminars in Thrombosis and Hemostasis, 2019)
Anticoagulant drugs comprise a specific subcategory of antithrombotic agents that act to inhibit blood coagulation at various stages, reducing clot development and ultimately lowering the risk of developing new-onset or recurrent thrombosis. Although the long history of anticoagulant drugs has been characteristically shaped by coumarin and heparin derivatives, a new generation of direct oral anticoagulants (DOACs), which specifically inhibit thrombin or activated factor X, combine many advantages of their progenitor drugs, and hence are prepotently revolutionizing the landscape of antithrombotic therapy. Several drugs (apixaban [BMS-562247], dabigatran [BIBR953], edoxaban [DU-1766], rivaroxaban [BAY 59–7939]) have already received widespread approval by national or supranational medicinal agencies. This narrative article provides a state-of-the-art for these and for several other DOACs at different stages of clinical evaluation (betrixaban, darexaban, eribaxaban, letaxaban, nokxaban), and certain others whose development has been discontinued (AZD-0837, fidexaban, LY517717, odiparcil, otamixaban, TTP889, and ximelagatran). What clearly emerges from our analysis is that DOACs sharing very similar mechanisms of action are still characterized by different efficacy and safety profiles. This not only depends on biochemical, biological, and pharmacokinetic characteristics, but also on lack of standardization between different clinical trials in terms of targeted disease, patient recruitment, sample size, duration and endpoints, as well as lack of harmonization around procedures used for drug licensing. These factors contribute to challenging the minds of physicians, who may find difficulty navigating their way through multiple indications, different pharmacological profiles, various side effects, and specific drug-to-drug interactions. Such considerations also burden laboratory professionals, who may face organizational and economic challenges in developing and/or implementing multiple assays to assess the pharmacodynamics (effect on coagulation) or pharmacokinetics (drug levels) of DOACs.
Keywords: hemostasis; thrombosis; anticoagulant; direct oral anticoagulants